2009
DOI: 10.1089/aid.2009.0016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Human Immunodeficiency Virus Type 1 among Children in Lima, Peru

Abstract: In Peru, there is a lack of information on molecular analysis in pediatric human immunodeficiency virus (HIV) infection. At present, the mother-to-child transmission rate is estimated at approximately 2-4%. The objective of this study was to assess the molecular epidemiology of HIV-1 in infected children. Children with suspected or confirmed pulmonary tuberculosis were evaluated at two public hospitals between 2002 and 2007. Whole blood samples were obtained from 90 HIV-positive children, who were confirmed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
1
8
1
Order By: Relevance
“…However, several studies on molecular characterization have shown that HIV-1 epidemics in South America are constituted not only by subtype B strains but also by subtype F strains, as well as recombinants between both subtype B and F. [7][8][9][10][11][12][13][14][15][16][17][18] In particular, the prevalence of BF recombinants is significantly higher than that observed for pure subtype F strains, reaching a prevalence similar to subtype B strains in some regions. 14 Considering the genetic distance between subtypes B and F, the presence of the BF recombinants in South America can only be explained by a second introduction of HIV-1 into the American Continent, independent of what occurred in the Caribbean/U.S.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies on molecular characterization have shown that HIV-1 epidemics in South America are constituted not only by subtype B strains but also by subtype F strains, as well as recombinants between both subtype B and F. [7][8][9][10][11][12][13][14][15][16][17][18] In particular, the prevalence of BF recombinants is significantly higher than that observed for pure subtype F strains, reaching a prevalence similar to subtype B strains in some regions. 14 Considering the genetic distance between subtypes B and F, the presence of the BF recombinants in South America can only be explained by a second introduction of HIV-1 into the American Continent, independent of what occurred in the Caribbean/U.S.…”
Section: Introductionmentioning
confidence: 99%
“…7 The high frequency of subtype B was persistent in Peruvian populations regardless of their sexual behavior and epidemiologic characteristics. 5,8,9,20 This information suggests that subtype B has gained important epidemiologic success in this country in contrast to other subtypes previously identified such as A and F. 7,9,21 In this work we have identified cases of subtypes A, C, and H (n = 4). In regard to subtype A, there is only one case reported in South America from a Peruvian heterosexual male patient, 7 who denied having had sexual contact with any individuals from other countries.…”
Section: Discussionmentioning
confidence: 74%
“…These findings indicate that these recombinants might have come from Argentina, Uruguay, Chile, or Brazil, countries where they have been reported in high frequency. 29 In addition, Carrion et al 9 found two cases of B/F recombination in HIV-infected children using a 1915-bp region of the gag-pol genes (positions from 1575 to 3565 based on the HXB2 strain). According to our data, we have not identified recombination B/F in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMA kits have been developed, initially to determine the viral genetic subtype of HIV-1 env sequences, and have been made freely available by the National Institutes of Health (NIH) AIDS Reagent Program (www.aidsreagent.org) and the National Institute for Biological Standards and Control (NIBSC) (www.nibsc.ac.uk), and used extensively worldwide (Apetrei et al, 1995; Avila et al, 2002; Bobkov et al, 1997; Bobkov et al, 1998; Bobkova et al, 2001; Buonaguro et al, 1995; Buonaguro et al, 2004; Cardoso et al, 2010; Carrion et al, 2009; Castro et al, 2003; Esteves et al, 2003; Esteves et al, 2002; Gadkari et al, 1998; Gaywee et al, 1996; Guimaraes et al, 2012; Hussein et al, 2000; Lakhashe et al, 2008; Lasky et al, 1997; Li et al, 1999; Loussert-Ajaka et al, 1998; Mandal et al, 2002; Mandal et al, 2000; Menu et al, 1999; Monteiro et al, 2009; Osmanov et al, 2002; Pando et al, 2007; Parreira et al, 2006; Ramalingam et al, 2005; Russell et al, 2000; Saad et al, 2006; Sabino et al, 1996; Sahni, Kapila, and Gupta, 2008; Sahni, Prasad, and Seth, 2002; Santiago et al, 1998; Sarkar et al, 2011; Sarrami-Forooshani et al, 2006; Sawadogo et al, 2003; Siddappa et al, 2004; Teixeira et al, 2004; Tripathy et al, 2005; Tscherning-Casper et al, 2000; Velarde-Dunois et al, 2000; Wasi et al, 1995b; Zhu et al, 1995). An HIV-1 gag subtyping HMA kit (Heyndrickx et al, 2000; Sengupta et al, 2005; Tatt, Barlow, and Clewley, 2000) is also available from the NIH and NIBSC, and assays have been developed for HIV-1 env -gp41 (Agwale et al, 2001) and tat (Diaz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%